Evolve : Teacher's Edition. With Test Generator. - Cocienda, Genevieve; Rimmer, Wayne; Robertson, Lynne; Simpson, Katy (Cambridge University Press, 2022)
EVOLVE is a six-level English course that gets students speaking with confidence. This interleaved Teacher's Edition with Test Generator Level 3 provides page-for-page teaching notes corresponding with the Student's Book. It includes answer keys for the Student's Book and Workbook, plus photocopiable worksheets for further practice of grammar, vocabulary, and speaking. A teacher development syllabus is woven throughout, providing opportunities to incorporate new teaching techniques in an easy and time-efficient way. In addition, suggested readings offer teachers the opportunity to expand their knowledge of the theories behind each technique. Test Generator provides ready-made unit tests, mid-level and end of level tests, in addition to a test-generating tool for creating bespoke tests.